How African Americans in Rural Areas Learn to Become Homeowners - Ulrica Jones-Hill (Adult Education Research Conference, 2004)
This study identified the process by which African Americans in rural areas become homeowners. By interviewing ten African Americans first time homebuyers living in rural middle Georgia and who purchased their homes through one of the Federal Rural Housing Programs within the past five years or less, it was discovered the homeowners used a variety of informal methods to gain information about homeownership.